Comparison of Anthropometric Indices in Relation to Physical Activity Levels Among University Students - Valdez López, Alison Gabriela; Quiroga, Elizabeth; Ballesteros López, Leonardo Gabriel (Revista Ecos de la Academia, 2025)
Anthropometric indices are essential for determining risks associated with malnutrition, whether due to weight deficit or excess, and promote well-being strategies depending on physical activity. This study analyzed the relationship between anthropometric indices: body mass index (BMI), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) and the level of physical activity in 646 students from the Technical University of Ambato, using the International Physical Activity Questionnaire (IPAQ). The results showed that BMI was the most affected by physical activity, presenting a significant correlation with moderate physical activity (P
Keywords: Anthropometry; higher education; physical exercise; nutritional status; students